(untitled) (Brazilian Journal of Radiation Sciences, 2018)
ABSTRACT Radiation therapy is a complex treatment modality involving several technological and professional resources as well as a large number of attributions of these professionals with a high degree of interdependence. Thus there are many possibilities of failure in the treatment process that may lead to an accidental exposure. So regulatory agencies have established guidelines in their regulations in order to prevent accidental exposures through security analysis planning and risk management. The System of EValuation of Risk in RAdiotherapy, also known as SEVRRA, is based on the risk matrix methodology and allows the risk assessment of radiation therapy facilities in a prescriptive way, highlighting events leading to high-risk levels and severe consequences for individuals. With SEVRRA it is also possible to establish an importance analysis of the barriers proposed to avoid or mitigate such events. This work aimed to demonstrate the application of SEVRRA for the risk management of radiation therapy facilities. The risk profile of the facility was determined by identifying the highest risk level events, and the barriers of greater impact for the overall risk level. After implementing some missing barriers in the original facility profile, it was achieved a reduction from 31% to 8% in the number of events leading to high-risk level, showing the effectiveness of SEVRRA for the risk management in radiation therapy facilities.